2009
DOI: 10.1086/600870
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Associated Inflammation and Toll‐Like Receptor Dysfunction Prime the Lungs for Pneumococcal Pneumonia

Abstract: Background Aging is associated with increased inflammation and risk for community-acquired pneumonia (CAP). Streptococcus pneumoniae co-opts the NFkB-regulated proteins Polymeric immunoglobulin receptor (pIgR) and Platelet-activating factor receptor (PAFr) to attach and invade cells. We sought to determine if aging and chronic inflammation was associated with increased pIgR & PAFr in the lungs and increased susceptibility to S. pneumoniae. Methods Lung protein and mRNA levels were quantitated using Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
125
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 47 publications
12
125
0
1
Order By: Relevance
“…TLR1 and -2 recognize cell wall-associated polysaccharide of pneumococcus (lipoteichoic acid) (31,32), and NOD2 recognizes peptidoglycan (22); both types of recognition upregulate inflammatory components, leading to macrophage influx and pathogen clearance. Furthermore, it has been reported in a mouse model of invasive pneumonia that protein levels of TLR1 and -2 are significantly decreased in aged compared to young adult mice following infection (7). We investigated the expression of these PRRs in the URTs of aged mice before and during colonization and found no statistical differences between age groups both before and during colonization in the epithelium.…”
Section: Figmentioning
confidence: 83%
See 2 more Smart Citations
“…TLR1 and -2 recognize cell wall-associated polysaccharide of pneumococcus (lipoteichoic acid) (31,32), and NOD2 recognizes peptidoglycan (22); both types of recognition upregulate inflammatory components, leading to macrophage influx and pathogen clearance. Furthermore, it has been reported in a mouse model of invasive pneumonia that protein levels of TLR1 and -2 are significantly decreased in aged compared to young adult mice following infection (7). We investigated the expression of these PRRs in the URTs of aged mice before and during colonization and found no statistical differences between age groups both before and during colonization in the epithelium.…”
Section: Figmentioning
confidence: 83%
“…Hinojosa et al (7) have recently shown an association of decreased protein levels of Toll-like receptor 1 (TLR1) and TLR2 in lung homogenates and increased levels of proinflammatory cytokines at baseline in elderly mice with higher mortality in a model of invasive pneumococcal pneumonia. These data suggest that there are innate defects in the lungs of elderly mice that likely contribute to increased risk and severity of pneumonia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of pneumococcal challenge, chronic upregulation of PAFr promotes bacterial invasion and predisposes SCD individuals to invasive disease (7,9,27). Statins are potent inhibitors of systemic inflammation (16,26,29) and thus might serve as a prophylactic measure for SCD individuals, potentially reducing the incidence and severity of pneumococcal infection.…”
Section: Discussionmentioning
confidence: 99%
“…34 Alterations in expression levels of multiple TLRs in the mouse brain during aging have also been reported. 35 Changes in MyD88 expression levels during aging may contribute to A␤ load in the brain.…”
Section: Myd88 Expression Decreases During Agingmentioning
confidence: 98%